The Influences of Open Communication by Senior Leaders and Legitimacy Judgments on Effective Open Innovation. (July 2023) - Wang, Chong; Cardon, Peter W.; Li, Ci-Rong; Li, Chun-Xuan
Firms increasingly recognize open innovation as a key aspect of their innovation strategies. This study of 200 open innovation managers showed that open internal communication by senior leaders drives higher legitimacy judgments, which in turn drives open innovation success. Further, legitimacy judgments mediate the relationship between open internal communication and open innovation success. Open external communication by senior leaders moderates the indirect relationship between open internal communication and open innovation success, with more open external communication strengthening the influence on open innovation success. These results suggest firm-level open communication by senior leaders is essential for project-level open innovation success.